The Impact of Higher Oil Prices on Global Liquidity - Al-Roubale, Amir (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Impact of Higher Oil Prices on Global Liquidity